CHALLENGES AND OPPORTUNITIES FOR ADOPTING ARTIFICIAL INTELLIGENCE IN EDUCATION : A LITERATURE REVIEW - Lista Meria; Saukani (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2023)
Technology and artificial intelligence (AI) are growing and their implementation is very fast. AI has become a part of our daily life. AI makes people start changing the way they think, work and learn. The education sector is one of the many affected by AI, even though its implementation faces many challenges and ethics. The aim of this study is to analyze the benefits, opportunities and challenges of AI in education. The method used in this study is a review of relevant literature on the research focus of AI in education. A total of 24 articles were analyzed to gain an in-depth understanding of the opportunities, benefits and challenges of adopting AI in education. The results show that the adoption of AI in education has been widely carried out in various countries and is increasingly emerging in the industrial era 4.0 coupled with the crisis due to the Covid-19 pandemic. AI in education creates new opportunities and challenges that require further hard work and innovation. This study also provides recommendations and directions for future research.